PENTINGNYA BERBAGI NASI DALAM MENINGKATKAN KEPEDULIAN MAHASISWA, MASYARAKAT DAN KOMUNITAS - Danang Nugroho; Eli Enjelina; Deni Sutia; Rafa Dita Putri Handiana; Nasran Aziza; Muthi Nur'afiah; Irfan Maulana Adjie (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The high percentage of unemployment and extreme poverty in Indonesia served as the impetus for this study. One issue that frequently comes up during the development process is unemployment. Growing rates of unemployment have the potential to impede progress and create issues in the social and economic spheres. Other factors that affect unemployment include rapid population increase, strong economic performance, and government involvement, particularly with regard to minimum wage policies. The absence of suitable work and the unwillingness of Indonesians to start their own businesses are the main causes of unemployment. In Indonesia, the number of people in productive age does not match the number of employment that are now available. Most Indonesians are now unemployed as a result.